Proteomic investigation of wheat intercellular washing fluid - Pós, Veronika (Acta Biologica Szegediensis, 2005)
The protein composition of wheat (Triticum aestivum L.) intercellular washing fluid was analysed to detect if there were changes in the protein pattern after fungal infection. The apoplast represents the first barrier to pathogens in the plant, and proteins which contribute to resistance against a given race of wheat leaf rust (Puccinia recondita f.sp. triticii) are expected to be found here. We compared the effect of leaf rust infection on two near-isogenic lines: the susceptible ‘Thatcher’ line and the corresponding near-isogenic Lr1-resistant line, which exhibits a hypersensitive response upon infection. Seven-day-old wheat seedlings were infected with Lr1 and the intercellular fluid was isolated at different times (1-7 days) after infection. Proteins were analysed by one- and two-dimensional gel electrophoresis followed by mass spectrometric analysis (MALDI-TOF) of selected protein species. Three apoplastic proteins, which appear earlier in the Lr1-resistant plants than in the ‘Thatcher’ line and which may therefore be involved in development of leaf rust resistance, were identified. One of the proteins is a glucan-endo-1,3-β-D-glycosidase (35413 Da), the second is a chitinase 1 enzyme (27077 Da) and the third one corresponds to the pathogenesis-related protein 1.1 (PR1.1, 17651 Da).